2011
DOI: 10.1080/00438243.2011.605841
|View full text |Cite
|
Sign up to set email alerts
|

How far to Conchucos? A GIS approach to assessing the implications of exotic materials at Chavín de Huántar

Abstract: Chavı´n de Hua´ntar has long been recognized as a site of pan-regional importance in the first millennium BCE Central Andes. Multiple lines of evidence link the site to costa, sierra and selva. Using exotic goods for which provenance is known -for example, obsidian, cinnabar, selected ceramics and marine shell -specific areas with which Chavı´n interacted can be identified. These interactions are considered in the context of distinct ways of thinking about Central Andean spacea least-cost transportation surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 20 publications
1
17
0
3
Order By: Relevance
“…Traveling from the Pacific Ocean to Chavín de Huántar would take about 6 days and would entail crossing the high mountain chains of the Cordilleras Blanca and Negra (Burger 1995;Contreras 2011). Therefore, the identification of Chavín worked bone artifacts as originating from the distant ocean or the local highlands provides an important layer of understanding about the ancient Chavinos and their material connections to distant places.…”
Section: Marine Mammal Remains From Archaeological Contextsmentioning
confidence: 96%
See 3 more Smart Citations
“…Traveling from the Pacific Ocean to Chavín de Huántar would take about 6 days and would entail crossing the high mountain chains of the Cordilleras Blanca and Negra (Burger 1995;Contreras 2011). Therefore, the identification of Chavín worked bone artifacts as originating from the distant ocean or the local highlands provides an important layer of understanding about the ancient Chavinos and their material connections to distant places.…”
Section: Marine Mammal Remains From Archaeological Contextsmentioning
confidence: 96%
“…While tropical goods such as furs and feathers are unlikely to preserve in highland sites, the remains of coastal bone artifacts document the varied economic ties that reached across the ancient Andean world. Much research has been conducted on the implications of Chavín's interaction with long-distance regions (Contreras 2011;Lumbreras 1989;Rick et al 2011). These studies are based on the known provenience of non-local material found at the site, such as cinnabar (Burger and Mendieta 2002), marine shells (Rick 2008;Sayre and Aldave Lopez 2010), and obsidian (Burger 1995).…”
Section: Implications Of the Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…Certainly, nothing like enclaves of non-local residents have been found, but neither has anything other than a tiny fraction of the residential architecture at Chavín been explored. It may be that the diversity of ritual architecture-and, similarly, the diverse origins of materials and offerings at the site (Contreras 2011;Druc 2004;Lumbreras et al 2003;Sayre, Miller, and Rosenfeld 2016)-is representative not just of pilgrimage but of a diversity of ceremonial practice. Heterarchy 2 may be reflected not just in the number of dispersed areas of ceremonial significance but also in the variety of practices apparently associated with those areas.…”
mentioning
confidence: 99%